(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
Corrosion inhibitors are considered one of the best techniques used to control the corrosion problem, but on the other hand, they pose environmental and economic burdens that constantly drive the search for alternatives, especially considering the environmental awareness that makes environmental safety a priority in modern society. So, this paper aims to review some of the recent literature to investigate the ability of plant extracts to inhibit corrosion in the oil industry, which is controlled with massive amounts of chemical inhibitors annually. Since low-carbon steel is the leading metal in this industry, the study of its corrosion behavior under the influence of these green inhibitors was selected as the starting point. Studies conducted in similar corrosive environments (NaCl environments) were particularly reviewed for more accurate comparisons and conclusions. The research discussed the factors affecting the performance of the plant-based inhibitors, starting from the effect of the preparation stage until the application conditions (extraction technique, inhibitor concentration, temperature, exposure time, velocity, and pH), besides some basic related theories. It was found that many plant extracts showed acceptable performance under different conditions, but there were some gaps and challenges that needed to be highlighted by future studies.